Performance evaluation of reworked weld joints - Ali, Aidy; Subramonian, Sivarao; Md Ali, Mohd Amran; Dhar Malingam, Sivakumar; Salleh, Mohd Shukor; Raja Abdullah, Raja Izamshah (SciPress Ltd., Switzerland, 2016)
This study presents the performance evaluation of reworked welded joint that have weld imperfections which may result the strength of the structures. Tensile, bending and shear tests have been performed to evaluate the performance and reliability of reworked joint. Their effects on the quality and performance of the reworked welded joint are depend on the requirements of the structure in use. This study is providing detailed examination of the mechanical properties of the carbon steel reworked welded joint by using shielded metal arc welding (SMAW) techniques.